Pengaruh Substitusi Silase Rumput Kume dengan Fodder Jagung Hidroponik terhadap Profil Darah Kambing Kacang Jantan - Laome, Tobe Obe; Yunus, Marthen; Ernawati, Luh Sri (Animal Agricultura, 2024)
This research aims to determine the effect of substitution of kume grass silage with corn fodder on the blood profile of male kacang goats. Using 3 male kacang goats aged 11-12 months with a body weight of 12-15 kg. This study used a Latin square design (RBSL) with 3 treatments for 3 periods. treatment given FCG0: 70% Kume grass silage + 30% concentrate; FCG1: 35% Kume grass silage + 35% corn fodder + 30% concentrate; FCG2: 20% Kume grass silage + 50% corn fodder + 30% concentrate. Blood parameters measured included Hemoglobin, PCV, Leukocytes and Erythrocytes. The collected data was processed by analysis of variance and continued with the Least Significant Difference test. The experimental results showed an increase in each variable as measured by hemoglobin 10.28-11.44g/dl, erythrocytes 9.26-10.14 x 104cell/mm³, leukocytes 10.36-12.32 x 50 cell/mm³ /ul PCV 30.83-34.33%. Statistical test results showed that substitution with corn fodder did not affect the blood profile (P>0.05) for hemoglobin, erythrocytes, leukocytes and PCV of kacang goat. It was concluded that using kume grass silage and corn fodder in a ratio of 35:35 and 20:50 could be used in male kacang goat rations.